Pemberdayaan Wanita Kelompok Tani Hutan Melalui Diversifikasi Produk Hasil Hutan Bukan Kayu (HHBK) - Shintawati Shintawati; Zulfahmi Zulfahmi; Ira Novita Sari; Livia Rhea Alvita (Jurnal Pengabdian UntukMu NegeRI, 2020)
KTH Agro Sumber Rejeki is one of the forest farmer groups located in the Register 40 production forest area in South Lampung Regency. This community service in the context of diversifying non-timber forest products (NTFPs), namely citronella oil. The purpose of this community service activity is to provide knowledge, technical production skills and quality requirements for citronella massage oil and telon oil, through empowering women from KTH Agro Sumber Rejeki. The method used in this PKM activity consisting of several stages, first technical guidance for making telon citronella oil and citronella sequence oil with 3 variants: natural, lemon and rose as well as counseling on herbal medicine quality requirements The effectiveness of PKM activities is evaluated by carrying out a pretest and postest. The average postest score was 83.53, an increase of 49.41 points from the pretest score with a total score of 100. The evaluation results showed that there was an increase in knowledge and technical skills in making telon citronella oil and citronella massage oil and also understanding the quality requirements of herbal medicines in women of KTH Agro Sumber Rejeki. . Keywords: Citronella, Massage Oil, Telon Oil